Customer Journey Analysis and Funnel Strategy Based on Social Media in Leather Craft SMEs - Fransiskus Xaverius Agung Perkasa Jampur; Bernadeta Wahyu Astri Pratita; Vinno Christmantara (Jurnal Penelitian, 2025)
This study analyzes the effectiveness of digital marketing strategies in a leather product SME in Malang City using two approaches: Customer Journey Mapping (CJM) and Marketing Funnel Analysis. The SME relies on Instagram and WhatsApp as its main interaction and sales channels but faces low user engagement and limited conversion of inquiries into transactions. A descriptive qualitative method was applied based on the analysis of customer conversations and social media insights. Data were collected from exported WhatsApp chats, Instagram Direct Messages (DMs), and customer interviews and surveys. The analysis included persona categorization, mapping of funnel stages (awareness, interest, consideration, conversion, loyalty), and identification of touchpoints, activities, emotions, and pain points, complemented by conversion rate calculations. The results show that most customers interact through WhatsApp (62.6%), with an overall conversion rate of 35.48%. The transition from interest to consideration recorded the highest drop-off, while customer loyalty and repeat orders emerged as the SME’s strongest asset. Interactions involving the owner achieved higher conversions than those managed by the admin, indicating the importance of personalized communication. CJM analysis also identified key pain points in sizing accuracy and product revisions, although these challenges were partly mitigated through after-sales support. Overall, the study concludes that digital marketing for SMEs can be strengthened by leveraging funnel and CJM-based insights to improve content quality, enhance communication performance, and optimize customer experience. These findings offer practical guidance for developing more targeted and data-driven digital marketing strategies within a business intelligence framework.